2012
DOI: 10.1088/0004-637x/752/1/48
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Solar Magnetic Bright Points Derived From Their Horizontal Motions

Abstract: The sub-arcsec bright points (BP) associated with the small scale magnetic fields in the lower solar atmosphere are advected by the evolution of the photospheric granules. We measure various quantities related to the horizontal motions of the BPs observed in two wavelengths, including the velocity auto-correlation function. A 1 hr time sequence of wideband Hα observations conducted at the Swedish 1-m Solar Telescope (SST ), and a 4 hr Hinode G-band time sequence observed with the Solar Optical telescope are us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 24 publications
13
80
0
Order By: Relevance
“…However, the features we studied display a much stronger super-diffusive behaviour. Super-diffusivity has also been reported by Abramenko et al (2011) andChitta et al (2012) in recent investigations. They deduced values of the diffusion index in a given type of region by averaging the displacements over all MBPs.…”
Section: Diffusion Indexsupporting
confidence: 70%
See 1 more Smart Citation
“…However, the features we studied display a much stronger super-diffusive behaviour. Super-diffusivity has also been reported by Abramenko et al (2011) andChitta et al (2012) in recent investigations. They deduced values of the diffusion index in a given type of region by averaging the displacements over all MBPs.…”
Section: Diffusion Indexsupporting
confidence: 70%
“…They reported the presence of super-diffusivity (as the only observed diffusion regime) for both quiet-Sun and active regions. This super-diffusivity was later confirmed by Chitta et al (2012) by tracking MBPs observed in wideband Hα.…”
Section: Introductionmentioning
confidence: 60%
“…Wang & Sheeley 1993;Schrijver et al 1996;Berger et al 1998;Hagenaar et al 1999;Chae et al 2008;Abramenko et al 2011;Chitta et al 2012;Giannattasio et al 2013Giannattasio et al , 2014aJafarzadeh et al 2014) at all accessible spatiotemporal scales, ranging from granulation (diameter 1 Mm and lifetime few minutes; Muller 1999;Hirzberger et al 1999;Del Moro 2004) to super-granulation (diameter 30 Mm and lifetime a day; Raju et al 1999;Srikanth et al 2000;Del Moro et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…It is clear that for frequencies >0.02 Hz (<50 s) the observational horizontal motions have more power, highlighting the fact that dynamics on short timescales may be very important in the generation of energetic kink and/or Alfvén wave phenomena. Images adapted from Chitta et al [2012b].…”
Section: Kink Wavesmentioning
confidence: 99%